2010
DOI: 10.1080/17429140903125848
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-resistant plant growth promoting rhizobacteria ameliorates sodium chloride stress on tomato plants

Abstract: Salinity is one of the major anthropogenic as well as environmental stresses that reduce plant growth. Results show that even after being adapted up to 6% sodium chloride (NaCl) concentration, all selected isolates were able to solubilize phosphate, and produce phytohormones, siderophores and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase enzyme. NT1 was found to exhibit the highest phosphate solubilization zones (25 mm), siderophore production (1000 mg ml (1 ) as well as ACC deaminase production (50 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(112 citation statements)
references
References 24 publications
7
104
1
Order By: Relevance
“…This effect may also be related to the production of EPS by Azotobacter isolate AzRDM2. Microbial EPS may both increase water holding capacity of soil and reduce water loss during desiccation (Tank and Saraf, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This effect may also be related to the production of EPS by Azotobacter isolate AzRDM2. Microbial EPS may both increase water holding capacity of soil and reduce water loss during desiccation (Tank and Saraf, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Glick et al (1998) showed that under different stresses using PGPR such as Pseudomonas fluorescence can alleviate the adverse effects of stress on plant growth. It has been indicated that some PGPR are able to produce polysaccharide products, binding Na + in the root zone and hence alleviating the effects of salt stress on plant and enhancing microbial growth and activities (Tank & Saraf 2010). Many studies have demonstrated that inoculation with AM fungi improves growth of plants under salt stress (Sharifi et al 2007).…”
mentioning
confidence: 99%
“…The identification was carried out using 16S rDNA sequencing and comparing them by BLAST database. Similar process was adopted in characterization by many earlier workers (Sturz et al 2000;Kuklinsky-Sobral et al 2004;Tank & Saraf 2010). …”
Section: Discussionmentioning
confidence: 99%
“…The hydraulic conductivity in such soils used to be poor and show high impedance to root growth (Qadir & Schubert 2002). These changes in soil properties affect the rhizospheric populations, thereby affecting the productivity of the commercial crops (Tank & Saraf 2010). Gladiolus is one such commercial monocotyledonous cut flower being cultivated for years along the river basins of major rivers of many countries (Wilfret 1992).…”
Section: Introductionmentioning
confidence: 99%